2016
DOI: 10.1103/physrevd.93.064019
|View full text |Cite
|
Sign up to set email alerts
|

Geodesic motion around a distorted static black hole

Abstract: In this paper we study geodesic motion around a distorted Schwarzschild black hole. We consider both timelike and null geodesics which are confined to the black hole's equatorial plane. Such geodesics generically exist if the distortion field has only even interior multipole moments and so the field is symmetric with respect to the equatorial plane. We specialize to the case of distortions defined by a quadrupole Weyl moment. An analysis of the effective potential for equatorial timelike geodesics shows that f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 55 publications
2
23
0
Order By: Relevance
“…In accordance with the study of the equatorial null geodesics around a distorted Schwarzschild black hole [52], where it was shown that null circular orbits in the black hole equatorial plane exist only if q ≥ q min , where q min = 1 − 2 cos(π/9) 24 cos 2 (π/9) + 20 cos(π/9) + 2 ≃ −0.020944533 ,…”
Section: B Quadrupole Distortionsupporting
confidence: 82%
See 2 more Smart Citations
“…In accordance with the study of the equatorial null geodesics around a distorted Schwarzschild black hole [52], where it was shown that null circular orbits in the black hole equatorial plane exist only if q ≥ q min , where q min = 1 − 2 cos(π/9) 24 cos 2 (π/9) + 20 cos(π/9) + 2 ≃ −0.020944533 ,…”
Section: B Quadrupole Distortionsupporting
confidence: 82%
“…The next term is the quadrupole, which is defined by a quadrupole moment a 2 . It defines the most dominant, nontrivial distortion field that allows for equatorial null geodesics [52], and it also captures the structure of many celestial objects that are nearly symmetric with respect to their equatorial plane. Here we shall consider only the quadrupole distortion and neglect the higher-order multipole moments.…”
Section: B Quadrupole Distortionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigating the geodesic motion around distorted black holes is a natural and active field of research, and focusing on the location of the ISCO is motivated by the astrophysical context. An example of a quite general, recent analysis in this direction is given in [23].…”
Section: Introductionmentioning
confidence: 99%
“…For static spacetimes, trapping of light has turned out to be a useful tool to prove uniqueness theorems; a static, asymptotically flat vacuum spacetime with a photon sphere as its inner boundary has to be a Schwarzschild spacetime [1,3]; analogous results holds for some cases with matter [2,25,26,27], and for one case even perturbative uniqueness was established [28], see also [20,21].…”
Section: Introductionmentioning
confidence: 99%